3D printed multilayer dielectric elastomer actuators. (8th February 2023) - Su, Sen; He, Tian; Yang, Hui
Abstract: In recent years, dielectric elastomer actuators (DEAs) have been widely used as flexible materials owing to their advantages of large strain, high efficiency, high energy density, and fast response in soft robots, grippers, and various artificial muscles. However, dielectric elastomers (DEs) are generally spin-coated and fabricated. The fabrication process is very complicated and cannot be realized quickly or in large quantities. In this study, we investigated a DEA that can be used for rapid fabrication via three-dimensional (3D) printing. This DE material can be rapidly cured using ultraviolet light and exhibits good mechanical and electrical properties. The material was modified based on CN 9021 (acrylate), and by adjusting the weight ratio of the diluent and crosslinker in the ink, viscosity and optimal mechanical properties that can be fabricated by 3D printing were obtained. The modified ink was then tested by printing it on a self-designed 3D printing platform, and the fabrication process was analyzed and improved to successfully produce DEA. The 3D printed single layer DEA can achieve a tip displacement of about 7.6 mm at the voltage of 2.5 KV. Comparing the driving performance of the DEA made by spin coating with that made by 3D printing, the DEA made by both fabrication methods showed the same performance. This 3D printing method greatly simplifies the DEA fabrication process and improves fabrication efficiency.